Wind and Wave Disturbances Compensation to Floating Offshore Wind Turbine Using Improved Individual Pitch Control Based on Fuzzy Control Strategy - Feng Yang; Qing-wang Song; Lei Wang; Shan Zuo; Sheng-shan Li (Abstract and Applied Analysis)
Due to the rich and high quality of offshore wind resources, floating offshore wind turbine (FOWT) arouses the attentions of many researchers. But on a floating platform, the wave and wind induced loads can significantly affect power regulation and vibration of the structure. Therefore, reducing these loads becomes a challenging part of the design of the floating system. To better alleviate these fatigue loads, a control system making compensations to these disturbances is proposed. In this paper an individual pitch control (IPC) system integrated with disturbance accommodating control (DAC) and model prediction control (MPC) through fuzzy control is developed to alleviate the fatigue loads. DAC is mainly used to mitigate the effects of wind disturbance and MPC counteracts the effects of wave on the structure. The new individual pitch controller is tested on the NREL offshore 5 MW wind turbine mounted on a barge with a spread-mooring system, running in FAST, operating above-rated condition. Compared to the original baseline collective pitch control (CPC) (Jonkman et al., 2007), the IPC system shows a better performance in reducing fatigue loads and is robust to complex wind and wave disturbances as well.